Nepal’s 2072 federal constitution: Implications for the governance of the agricultural sector - Kyle, Jordan; Resnick, Danielle (International Food Policy Research Institute, 2016)
In this paper we explore the implications of Nepal’s new federal Constitution—passed in September 2015—for governance of the agricultural sector. Agriculture is the backbone of the Nepali economy, providing a livelihood for approximately two-thirds of the population, contributing one-third of the country’s GDP, and constituting more than half of the country’s exports. In transitioning from a unitary to a federal republic—with greater authority and autonomy granted to subnational units of government—it is of paramount importance to ensure that the agricultural sector is guided by coordinated planning, retains sufficient human capacity, and receives adequate fiscal resources. These considerations are particularly important given that the governance of Nepal’s agricultural sector already suffers from poor coordination, low human resources capacity, and inadequate financial resources. Addressing these issues may become more difficult under a federal structure. This paper begins by laying out the main challenges for agricultural governance in Nepal under the current structure. To do so, it relies on an original survey of 100 district agricultural and livestock officers in charge of local agricultural service delivery in Nepal as well as perspectives collected through more than two dozen semi-structured interviews with officials from the Ministry of Agricultural Development, the Ministry of Livestock Development, civil society, the private sector, and donors. Because Nepal is embarking on a pathway to more decentralized governance, which has been well-trodden by a number of other countries, the paper proceeds by examining five case studies, drawing lessons from India, Indonesia, Kenya, Malaysia, and South Africa. Based on these analyses, the paper offers policy recommendations on how the sector can be restructured to meet the constitutional provisions, while simultaneously ensuring that the government can deliver on its long-term objectives to develop the agricultural sector.